Effect of compression stockings on physiological responses and running performance in division III collegiate cross-country runners during a maximal treadmill test - Rider, B. C.; Coughlin, A. M.; Hew-Butler, T. D.; Goslin, B. R. (The Journal of Strength and Conditioning Research, 2014)
There is a growing trend for runners to use compression stockings (CS) to improve performance. The purpose of this study was to determine the effect of CS on physiological variables associated with running performance. Participants were 10 NCAA division III cross-country runners. The study used a randomized, crossover design with 2 conditions (with CS and without CS). Both conditions consisted of a maximal treadmill test that involved 3-minute stages of increasing speed and incline, separated by a minute and one-half walking recovery stage. Seven days later, the participants repeated the maximal test but switched CS condition. Heart rate, blood lactate (BLa), blood lactate threshold, maximal oxygen consumption (VO2max), respiratory exchange ratio, rating of perceived exertion, and time to fatigue were measured. Before and during the maximal treadmill tests, the variables showed no significant difference (p < 0.05) between the CS conditions. Blood lactate was lower while wearing CS when measured during recovery at the 1-minute (CS = 13.3 ± 2.9 mmol/L, non-CS = 14.8 ± 2.8 mmol/L, p = 0.03) and the 5-minute (CS = 11.0 ± 2.7 mmol/L, non-CS = 12.8 ± 2.8 mmol/L, p = 0.02) periods. Time to fatigue was longer without CS (CS = 23.570 ± 2.39 minutes, non-CS = 23.93 ± 2.49 minutes, p = 0.04). These findings suggest that CS may not improve running performance, but could lend credence to certain manufacturers' claims of improved recovery through lower BLa values after exercise.